2001
DOI: 10.2174/0929867013373435
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Reactions to Fluoroquinolones. An Overview on Mechanistic Aspects

Abstract: This review focuses on the most recent research findings on adverse reactions caused by quinolone antibiotics. Reactions of the gastrointestinal tract, the central nervous system (CNS) and the skin are the most often observed adverse effects. Occasionally major events such as phototoxicity, cardiotoxicity, arthropathy and tendinitis occur, leading to significant tolerability problems. Over the years, several structure-activity and side-effect relationships have been developed, in an effort to improve overall a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
131
2
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(144 citation statements)
references
References 3 publications
2
131
2
9
Order By: Relevance
“…5 However, few studies had reported more gastrointestinal than neurological ADRs. 6 Our findings are contrasting to postmarketing surveillance of ciprofloxacin alone, as well as those of ciprofloxacin, norfloxacin, and ofloxacin showed a preponderance of ADR reporting to skin and appendages, followed by neurological and gastrointestinal disorders.…”
Section: Discussioncontrasting
confidence: 99%
“…5 However, few studies had reported more gastrointestinal than neurological ADRs. 6 Our findings are contrasting to postmarketing surveillance of ciprofloxacin alone, as well as those of ciprofloxacin, norfloxacin, and ofloxacin showed a preponderance of ADR reporting to skin and appendages, followed by neurological and gastrointestinal disorders.…”
Section: Discussioncontrasting
confidence: 99%
“…The reported side effects associated with the use of these antibiotics include tendon pain and/or rupture in a small proportion of patients, principally affecting the Achilles tendons (1). Although other adverse reactions, which have been observed in the central nervous system and gastrointestinal tract, may involve antagonism of amino acid neurotransmitter receptors (2), the cellular interactions underlying the effects of fluoroquinolones on the tendons are not clear. Inflammation of the paratenon and degenerative changes in tendon cells have been noted in studies of fluoroquinolone-treated animals (3,4).…”
mentioning
confidence: 99%
“…Proconvulsant activity of ciprofloxacin and ofloxacin is due to inhibition of GABA-A channels and lowering of seizure threshold as reported by De Sarro and De Sarro 2001. [4] Caffeine acts by blocking adenosine receptor in the brain. [22] Potentiation of proconvulsive action of fluoroquinolone is seen on addition of caffeine.…”
Section: Chemoconvulsion Modelmentioning
confidence: 99%
“…Adverse effects on central nervous system (CNS) also need to be explored as some CNS effects have been observed in some animal and clinical studies. [2][3][4][5] A headache and dizziness are common symptoms in humans. Hallucinations, delirium, and seizures have been observed in 0.9-11% of patients.…”
Section: Introductionmentioning
confidence: 99%